Efektivitas PenamEfektivitas Penambahan Probiotik Komersial “Lacto-Bact” Pada Pakan Terhadap Pertumbuhan Ikan Lele Dumbo (Clarias gariepinus)bahan Probiotik Komersial “Lacto-Bact” Pada Pakan Terhadap Pertumbuhan Ikan Lele Dumbo (Clarias gariepinus) - Safratilofa, Safratilofa; Syahrizal, Syahrizal; Ahmad, Aisah (Jurnal Akuakultur Sungai dan Danau, 2024)
This research aims to determine the effectiveness of adding probiotics to feed on the growth of African catfish (C. garipenus). The study used a completely randomized design with 4 treatments and 3 replications, including feed without probiotics (A/control), Probiotic dose 4 ml/kg feed (B), Probiotic dose 8 ml/kg feed (C) and Probiotic dose 12 ml/kg feed (D). The test fish that will be used are African catfish seeds measuring 4.22 cm - 4.71 cm. The main test material that will be used is probitic (Lacto-Bact) in the form of flour which is dissolved in distilled water at a dose of 2% kg of feed. The containers used in this research were 12 aquariums measuring 70x40x30 cm with a water volume of 24 L. The parameters observed in this research included feed conversion ratio (FCR), absolute weight growth (PBM), absolute length growth (PPM), survival, proximate test of feed and water quality. The results of the research showed that there was a very significant development in the length and average length. The initial weight of fish at stocking ranged from 0.83-0.89 g/head and increased by 184.89%-333.88% to 2.37-3.81 g/fish. The initial average length of the test fish at the time of stocking ranged between 4.22-4.72 cm/fish and increased by 59.14% - 67.39% to 6.72 - 7.89 cm/fish. The FCR value ranges between 1.33-3.23. PBM values ranged from 1.54-2.93 g/head. PPM values range between 2.50-3.18 cm/head. The SR value ranges between 81.39% - 88.89%. The highest protein content in treatment D was 23.6015%. Feed protein for all types of feed treatment varies relatively in the range of 17.5058%-23.6015%. The results of the water quality analysis of the rearing media show that the water quality is still within the appropriate range for rearing African catfish.